2020
DOI: 10.3892/etm.2020.9033
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑193b regulates human ovarian cancer cell growth via targeting STMN1

Abstract: Ovarian cancer is the eighth most common malignancy among women worldwide. Ovarian cancer exhibits no obvious symptoms in the early stage of tumorigenesis and currently, no effective methods for the early detection and treatment of ovarian cancer have been established. Therefore, the identification of novel targets is critical to the early diagnosis and clinical treatment of ovarian cancer. microRNAs (miRs) are small non-coding RNAs, which serve an important biological role in a number of physiological process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, Liu et al showed that a nomogram constructed from the mRNA expression of plasma HSP90AA1 could predict the risk of breast cancer incidence and metastasis [ 41 ]. Additionally, tubulin STMN1 is up-regulated and has de-stabilizing activity in various tumor tissues [ 42 ], which is associated with the proliferation, invasion, and migration of gastric cancer [ 43 ], ovarian cancer [ 44 ], and HCC [ 45 ]. Interestingly, in the DRGPI risk assessment model constructed by our team, the coefficients of PON1 and ADH4 were negative.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Liu et al showed that a nomogram constructed from the mRNA expression of plasma HSP90AA1 could predict the risk of breast cancer incidence and metastasis [ 41 ]. Additionally, tubulin STMN1 is up-regulated and has de-stabilizing activity in various tumor tissues [ 42 ], which is associated with the proliferation, invasion, and migration of gastric cancer [ 43 ], ovarian cancer [ 44 ], and HCC [ 45 ]. Interestingly, in the DRGPI risk assessment model constructed by our team, the coefficients of PON1 and ADH4 were negative.…”
Section: Discussionmentioning
confidence: 99%
“…miR-193b-3p is involved in different biological and pathological processes. For instance, Li et al reported that miRNA-193b suppresses proliferation and induces apoptosis in ovarian cancer [ 32 ]. miR-193b-3p also inhibits neuroblastoma cell growth [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in FaDu cancer cells (HNSCC) in vitro knockdown of miR-193b substantially reduced cell proliferation and migration, as well as tumor formation in an animal model [ 35 ]. In contrast, in human ovarian cancer cells it has been suggested that miR-193b could act as tumor suppressor by inhibiting cell proliferation and inducing apoptosis [ 36 ]. The lesson to learn from such apparently contradictory observations is that the specific functional role of miRNAs (oncogene or tumor suppressor gene) may vary depending on the tumoral tissue type.…”
Section: Discussionmentioning
confidence: 99%